2011
DOI: 10.1080/10810730.2011.551993
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes Toward Direct-to-Consumer Advertisements and Online Genetic Testing Among High-Risk Women Participating in a Hereditary Cancer Clinic

Abstract: Genetic testing for the breast cancer genes 1/2 (BRCA 1/2) has helped women determine their risk of developing breast and ovarian cancer. As interest in genetic testing has grown, companies have created strategies to disseminate information about testing, including direct-to-consumer advertising (DTCA) and online genetic testing. This study examined attitudes toward DTCA and online testing for BRCA among 84 women at a high-risk clinic as well as additional factors that may be associated with these attitudes, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 57 publications
1
14
0
Order By: Relevance
“…Although the counsellors in the study by Giovanni et al (2010) were equally divided on whether genetic testing should be limited to a clinical setting, over half of them agreed that it was acceptable if counselling was provided. This finding is supported by previous research (Wilde et al 2011;Gray et al 2011;Perez et al 2011) that there was a preference among consumers to access genetic tests via a health professional. In one US study, among the health professionals who were aware of DTC testing, 43 % cited benefits such as the ability to offer relevant screening tests at an earlier age and to offer more frequent screening as appropriate (Powell et al 2011).…”
Section: Discussionsupporting
confidence: 87%
“…Although the counsellors in the study by Giovanni et al (2010) were equally divided on whether genetic testing should be limited to a clinical setting, over half of them agreed that it was acceptable if counselling was provided. This finding is supported by previous research (Wilde et al 2011;Gray et al 2011;Perez et al 2011) that there was a preference among consumers to access genetic tests via a health professional. In one US study, among the health professionals who were aware of DTC testing, 43 % cited benefits such as the ability to offer relevant screening tests at an earlier age and to offer more frequent screening as appropriate (Powell et al 2011).…”
Section: Discussionsupporting
confidence: 87%
“…For instance, a study of cystic fibrosis patients and parents in Belgium demonstrated considerable skepticism toward commercial companies, with 41% of participants believing that the law should forbid genetic testing being offered directly to consumers . Similarly, among 86 women at high risk for breast and ovarian cancer in the United States (Connecticut), only 20% reported support for accessing genetic testing for breast cancer through online services …”
Section: Discussionmentioning
confidence: 99%
“…Individuals who seek this more predictive type of genetic testing have personal and/or familial contact with the disease. This experience can shape their general awareness, attitudes and responses to testing (Molinger et al 1998; Perez et al 2011; Sussner et al 2010). Although our college smokers demonstrated general awareness of genetic susceptibility testing and specific knowledge of genetic concepts, several themes emerged that require careful consideration among health professionals looking to use genetic testing as a vehicle to motivate disease prevention or behavior change.…”
Section: Discussionmentioning
confidence: 99%